دراسة الشروط المؤثرة على تحديد قيم عوامل الحسم لاستثمارات مشاريع النقل في سورية - عمران جمال; بدر يعرب; علي ميس شهاب (Latakia University Journal -Engineering Sciences Series, 2019)
يقدم هذا البحث مساهمة لدراسة دعم عملية اتخاذ القرار في استثمارات مشاريع النقل( الطرق) في سورية عن طريق تحديد عامل هام هو عامل معدل الحسم الـ (Discount Rate)، هذا العامل الذي يلعب دوراً كبيراً في اعتماد المشاريع الاستثمارية الخدمية كمشاريع مجدية ، ومعرفة العوامل المؤثرة في تغيير قيمه، وذلك من خلال الاطلاع على الأسس والمعايير المتبعة في دراسة الجدوى الاقتصادية لمشاريع الطرق في بعض الدول ، وكيفية تقدير عامل معدل الحسم والعوامل المؤثرة فيه، ومن ثم إجراء دراسة تحليلية وإحصائية لمجموعة دراسات جدوى اقتصادية خاصة بمشاريع طرق محلية لدى المؤسسة العامة للمواصلات الطرقية, خططها التنفيذية تقع بين عامي 2006-2008. وبالتالي فإن الهدف من هذا البحث هو معرفة مجموعة العوامل الأكثر تأثيراً على قيم عامل الحسم في سورية، كما يتضمن اقتراح منهجية دراسة جدوى اقتصادية لمشروع نقل (طريق) تتضمن المعايير المناسبة . This research provides a contribution to support the process of decision-making investments in transport projects (roads) in Syria, by identifying important factor is the factor of the discount rate (Discount Rate), which plays a major role in the adoption of investment projects meaningful service projects, and knowledge of the factors affecting the change of values, through access to the bases and criteria for economic feasibility study for road projects in some countries, how to estimate a discount rate and the factors influencing it, and then conduct statistical and analytical study of the feasibility studies of a group of special economic projects with the local ways projects in Syria of the General Establishment for road transport, is the executive plans between 2006-2008. . Therefore, the objective of this research is to know the range of factors impact on the values of the most decisive factor in Syria, as well as suggest a methodology to study the economic feasibility of the transport project (road) include appropriate standards.